Public health impact of UK COVID-19 booster vaccination programs during Omicron predominance. (31st December 2023) - Mendes, Diana; Chapman, Ruth; Aruffo, Elena; Gal, Peter; Nguyen, Jennifer L.; Hamson, Libby; Di Fusco, Manuela; Czudek, Carole; Yang, Jingyan
ABSTRACT: Background: We aimed to estimate the public health impact of booster vaccination against COVID-19 in the UK during an Omicron-predominant period. Research design and methods: A dynamic transmission model was developed to compare public health outcomes for actual and alternative UK booster vaccination programs. Input sources were publicly available data and targeted literature reviews. Base case analyses estimated outcomes from the UK's Autumn–Winter 2021–2022 booster program during January–March 2022, an Omicron-predominant period. Scenario analyses projected outcomes from Spring and in Autumn 2022 booster programs over an extended time horizon from April 2022–April 2023, assuming continued Omicron predominance, and explored hypothetical program alternatives with modified eligibility criteria and/or increased uptake. Results: Estimates predicted that the Autumn–Winter 2021–2022 booster program averted approximately 12.8 million cases, 1.1 million hospitalizations, and 290, 000 deaths. Scenario analyses suggested that Spring and Autumn 2022 programs would avert approximately 6.2 million cases, 716, 000 hospitalizations, and 125, 000 deaths; alternatives extending eligibility or targeting risk groups would improve these benefits, and increasing uptake would further strengthen impact. Conclusions: Boosters were estimated to provide substantial benefit to UK public health during Omicron predominance. Benefits of booster vaccination could be maximized by extending eligibility and increasing uptake.